Postulates and Proposals of Members of the Polish Government-in-Exile for Poland’s Economic Security in the Context of the Reconstruction of the State in 1944–1945: Selected Examples - Landmann, Tomasz; Olbrycht, Paweł (Historia i Polityka, 2023)
The article aims to indicate selected, postulated directions of Poland’s economic recovery in the early years after World War II, considering the contribution made by the Polish Government-in-Exile (Government of the Republic of Poland in Exile). The analysis includes a query of archival documents from 1944–1945 and a review of scientific literature. The thesis has been put forward that the substantive developments from the years 1944–1945 prepared by the Government of the Republic of Poland in Exile may constitute a valuable cognitive source for the analysis of possible directions of reconstruction and development of the Polish economy after the destruction caused by the events of World War II. It has been shown that the Government of the Republic of Poland in Exile created numerous studies on the economic recovery of the country after World War II, even before the armed conflict formally ended. Many of the valuable guidelines referred to the reconstruction and development of the coal mining industry, oil industry, and forest management.